A numerical method to compute flexible vertical responses of containerships in regular waves. (15th December 2022) - Wang, Haixing; Duan, Wenyang; Chen, Jikang; Ma, Shan
Abstract: In this paper, a series of simulations of hydroelastic problems of containerships are conducted by a nonlinear 3D panel method which is based on the generalized Taylor Expansion Boundary Element Method (TEBEM). In the structure part, the Transfer Matrix Method is selected to perform a modal analysis which provides key parameters of hydroelastic calculation. In the hydrodynamic part, the nonlinearities arising from the variations of instantaneous wetted surface area are considered in the solutions of hydrostatic restoring forces as well as 1st order incident wave forces. Meanwhile, an extended Modified Logvinovich Model (MLM) is presented to predict the slamming forces due to the large-amplitude incident waves. The numerical predictions of the hydroelastic responses of a 6750-TEU containership and S175 in regular waves are presented. The effects of wave steepness and sailing speed as well as the variation characteristics of load components against with wave direction are studied. The numerical and experimental results are in acceptable agreement which proves the accuracy of the proposed method.